Hydraulic Performance Analysis of Open Channel Flow Using HEC-RAS Modeling - Susbandro, Zakaria; Phuong, Nguyen Thi Minh (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
Open channel flow analysis plays a critical role in hydraulic engineering, particularly in river management, flood mitigation, and infrastructure design. Recent advancements in numerical modeling have positioned HEC-RAS as one of the most widely adopted tools for hydraulic performance evaluation. This study aims to analyze the hydraulic performance of open channel flow using HEC-RAS modeling by synthesizing empirical findings from multiple case studies and applying a structured hydraulic simulation framework. The research employs a numerical modeling approach using steady and unsteady flow simulations, calibrated with Manning’s roughness coefficients and cross-sectional survey data. The results indicate that HEC-RAS provides reliable estimations of water surface elevation, flow velocity, and energy losses across diverse channel geometries. Comparative analysis with previous studies demonstrates strong consistency between simulated and observed hydraulic parameters. The findings confirm that HEC-RAS is effective for evaluating open channel performance under varying hydraulic conditions and supports informed decision-making in channel design, flood risk management, and hydraulic infrastructure optimization. This study contributes to the growing body of evidence supporting HEC-RAS as a robust and practical hydraulic modeling tool for open channel systems.